The Analysis of Students’ Difficulties in Reading Comprehension on Narrative Text at Eleventh Grade Students of SMAN 2 Muaro Jambi - Abida, Rahma; Munawwaroh, Khidayatul; Aisyah, Siti (Universitas Batanghari Jambi, 2024)
The purpose of this study was to determine the students’ difficulties in reading comprehension on narrative text at Senior High School 2 Muaro Jambi. This research was conducted at Senior High School Number 2 Muaro Jambi. This research is categorized as a quantitative research design with a descriptive qualitative approach. The subject of this research was 30 students of class eleventh. This research instrument used questionnaires to collect the data. The questionnaire contains 25 statements of the 25 statements. The result of this study is that the students of eleventh grade at Senior High School Number 2 Muaro Jambi in reading comprehension on narrative text have difficulty in making inferences, identifying references, finding specific information, and the understanding meaning of words or vocabulary.